Rules of Redistribution and Foreign Aid: A Proposal for a Change in the Rules Governing Eligibility for Foreign Aid - Branko Milanovic (Intervention. European Journal of Economics and Economic Policies, 2008)
When income is redistributed at national level, the minimum requirement is that the transfers should be progressive, that is flow from richer to poorer individuals. The same rule should hold at the global level: it is not sufficient that transfers be from a richer to a poorer country. But normally we do not know who are the taxpayers who finance international aid nor who are the beneficiaries of aid. We can nevertheless establish the rules such that the likelihood of a globally regressive transfer is minimized. This implies taking into account countries- national income distributions: penalizing countries with highly unequal distributions since there exists a non-trivial probability that the transfers may be received by people richer than rich countries- taxpayers. Some rules for changing eligibility criteria for aid are proposed.
Keywords: F35; D3; 330; aid; redistribution; global income distribution